Vascular System Modeling in Parallel Environment - Distributed and Shared Memory Approaches - Jurczuk, K.; Kretowski, M.; Bezy-Wendling, J. (IEEE transactions on information technology in biomedicine, 2011)
This paper presents two approaches in parallel modeling of vascular system development in internal organs. In the first approach, new parts of tissue are distributed among processors and each processor is responsible for perfusing its assigned parts of tissue to all vascular trees. Communication between processors is accomplished by passing messages, and therefore, this algorithm is perfectly suited for distributed memory architectures. The second approach is designed for shared memory machines. It parallelizes the perfusion process during which individual processing units perform calculations concerning different vascular trees. The experimental results, performed on a computing cluster and multicore machines, show that both algorithms provide a significant speedup.